In vivo CRISPR screens identify a dual function of MEN1 in regulating tumor–microenvironment interactions - Su, P; Liu, Y; Chen, T; Xue, Y; Zeng, Y; Zhu, G; Chen, S; Teng, M; Ci, X; Guo, M; He, MY; Hao, J; et al. (Nature Research, 2024)
Functional genomic screens in two-dimensional cell culture models are limited in identifying therapeutic targets that influence the tumor microenvironment. By comparing targeted CRISPR–Cas9 screens in a two-dimensional culture with xenografts derived from the same cell line, we identified MEN1 as the top hit that confers differential dropout effects in vitro and in vivo. MEN1 knockout in multiple solid cancer types does not impact cell proliferation in vitro but significantly promotes or inhibits tumor growth in immunodeficient or immunocompetent mice, respectively. Mechanistically, MEN1 knockout redistributes MLL1 chromatin occupancy, increasing H3K4me3 at repetitive genomic regions, activating double-stranded RNA expression and increasing neutrophil and CD8+ T cell infiltration in immunodeficient and immunocompetent mice, respectively. Pharmacological inhibition of the menin–MLL interaction reduces tumor growth in a CD8+ T cell-dependent manner. These findings reveal tumor microenvironment-dependent oncogenic and tumor-suppressive functions of MEN1 and provide a rationale for targeting MEN1 in solid cancers.